Constituent Perceptions of Political Representation: How Citizens Evaluate Their Representatives - Lauermann, Robin M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book examines the nature of representation in democracy, focusing specifically on the factors shaping constituent evaluations of the US House Representatives and the resulting implications for government.
Keywords: Science; Science; Science, general